PERSEPSI MASYARAKAT TENTANG PEMBERIAN VAKSIN COVID-19 DI KELURAHAN SUNGAI TIUNG KECAMATAN CEMPAKA KOTA BANJARBARU - Fauziah, Erna; Mariana, Evi Risa; Sajidah, Ainun (Jurnal Skala Kesehatan, 2022)
ABSTRACT: Corona Virus Disease (COVID-19) is a new type of virus that attacks the body’s immunity and can cause death. The virus spreads quickly in various regions of Indonesia, placing in the highest number of cases in Southeast Asia and Asian region. As the positive cases increases, the government must immediately take policies so that transmissions of this disease are reduced. One of the policies is the provision of vaccines to the community. This aims to determine public perceptions of the administration of vaccine in Sungai Tiung Village, Cempaka District, Banjarbaru City. This data is describing on perceptions from the public based on age, education and occupation about the vaccine. The population of this research is those who live in RT. 14/004 Sungai Tiung Village, Cempaka District, Banjarbaru City, using probability sampling technique, namely simple random sampling, obtained 50 people who are willing to become respondents. The results of the study are presented in the form of frequency distribution table. The results showed that there were still 4 people (8%) public perception based on age had negative perceptions, public perceptions about the vaccine giving based on education still had negative perceptions as many as 1 person (2%) and people’s perception about the delivery of vaccine based on work there are still 9 people who have a negative perception (18%). The researcher suggests the Public Health Center, especially the health promotion, to increase socialization and education about transmission of COVID-19 and benefits of the vaccine. Key words: Public Perception, COVID-19 Vaccine